SELECTIVE ELECTROEXTRACTION OF BASE METALS FROM LEACHING SOLUTIONS OBTAINED DURING THE RECYCLING OF WASTE PRINTED CIRCUIT BOARDS. II. SELECTIVE POTENTIOSTATIC ELECTRODEPOSITION OF COPPER, TIN AND LEAD - FRÎNCU, Marian-Iosif; COVACI, Eniko; DORNEANU, Sorin-Aurel; ILEA, Petru (Studia Universitatis Babeș-Bolyai Chemia, 2021)
This paper presents our results concerning the feasibility of selective potentiostatic electroextraction of copper, tin and lead from leaching solutions obtained during the recycling of base metals from waste printed circuit boards. Applying this protocol, in a first stage, the concentration of Cu ions from the leaching solutions can be lowered, with acceptable efficiency, below 0.5 g/L. To avoid the contamination of Sn-Pb alloys with Cu, an intermediary step of Cu cementation on metallic Sn were proposed and tested. Finally, the potentiostatic selective electrodeposition protocol was successfully applied for the electroextraction Sn-Pb alloys. The experiments were performed in real leaching samples, using a Fisher type electrode as cathode. The obtained experimental results demonstrate that, controlling rigorously the imposed potential and corelating them with the solution composition, high purity Cu and Sn-Pb alloys deposits can be obtained, maximum contents of 99.96%, 99.83% and 82.62% being evaluated for Cu, Sn and Pb, respectively.